PHILOSOPHICAL AND THEOLOGICAL RELEVANCE OF EVOLUTIONARY ANTHROPOLOGY ([S.l.])
1 online resource
Keywords: This book explores the philosophical and theological significance of evolutionary anthropology and includes diverse approaches to the relationship between evolution, culture, and religion. Particular emphasis is placed on the work of Michael Tomasello, who contributes an opening chapter that tackles the role of religion in his natural history of human thinking and human morality. The first section of the book considers the philosophical foundations of evolutionary anthropology and shows that evolutionary anthropology is open to a multitude of philosophical analyses. The second part offers theological perspectives on the relationship between evolutionary and theological anthropology and between evolution and religion. The volume also reflects more broadly on the complex relationship between religion and science in the contexts of late-modern societies. It makes a significant contribution to the religion and science debate and offers performative evidence that an interdisciplinary discussion between theologians, philosophers, and natural scientists is feasible.